Mediating effects of behavioral intention between 3g predictors and service satisfaction - Ismail Sheikh Yusuf Ahmed Dhaha; Sheikh Ali, Ali Yassin (Universiti Kebangsaan Malaysian, 2014)
This paper looks at the factors that affect the adoption and satisfaction with third generation (3G) mobile phones among students at a private university in Somalia from the perspective of the Unified Theory of Acceptance and Use of Technology (UTAUT. Specifically, the objectives of the study are to 1) examine the effect of performance expectancy on students’ intention to adopt 3G; 2) explore the effect of effort expectancy on students’ intension; 3) look at the effect of social influence on students’ intention; 4) examine the effect of perceived expense on students’ intention; 5) test the effect of intention on students’ satisfaction with the service; and finally 6) test the mediating effect of intention between 3G predictors and satisfaction with the service. The study uses proportionate stratified random sampling procedure, where the faculty and gender were the main strata. The data were collected in June 2013 and a total of 395 students responded to the study. The data was analyzed using SPSS version 17.0 to answer research objectives and test its hypotheses. Using multiple Step-Wise regression, the results suggested that performance expectancy (β=.158, t=2.850, p=.005), effort expectancy (β=.106, t=2.094, p=.037), social influence (β=.358, t=6.888, p=.000), and perceived expense (β=.165, t=3.872, p=.000) had significant and positive effects on students’ intention to adopt 3G mobile technology. However, social influence (β=.358) was the best predictor for the students’ intention followed by perceived expense (β=.165). Furthermore, behavioral intention significantly mediated the relationships of predictors with satisfaction. Implications and future research scope are discussed.